Hematological parameters for the Brycon orbignyanus Valenciennes, 1850 (Osteichthyes: Characidae) intensively bred - Tavares-Dias, Marcos; Ruas de Moraes, Flávio (HIDROBIOLÓGICA, 2017)
This paper determined red blood cell number, total thrombocyte count, and total leukocyte, and differential counts for young Brycon orbignyanus Valenciennes 1849 (Characidae) maintained in fish farming ponds. Mean values and range obtained were as follows: red blood cell count 3.283 (2.110-4.235) x 106 /µl, hemoglobin 10.7 (8.4- 13.1) g/dl, hematocrit 40.2 (35.0-47.0) %, mean corpuscular volume 125.0 (91.5-199.1) fl, mean corpuscular hemoglobin concentration 26.9 (19.5-35.6) g/dl, total thrombocyte count 25,743.0 (11,228.0-54,152.0) µl, total leukocyte count 23,290.0 (9,601.0-37,520.0) µl, lymphocytes 3,642.0 (709.0-9,005.0) µl, neutrophils and heterophils 18,178.0 (7,488.0-29,783.0) µl and monocytes 1,471.0 (147.0-4,976.0) µl. These results found should be useful for evaluation of health status of this fish, when in intensive breeding or other cultivation forms, in addition to serving for comparison of this species in a natural environment.